Dual-layer detector spectral CT versus magnetic resonance imaging for the assessment of iron overload in myelodysplastic syndromes and aplastic anemia. - Ma, Quanmei; Hu, Juan; Yang, Wei; Hou, Yang (Japanese Journal of Radiology, 2020)
Background: The purpose of this study is to investigate the performance of dual-layer detector spectral CT for iron deposition compared to magnetic resonance imaging (MRI) T2* imaging.Methods: Thirty-one patients with a clinical history of myelodysplastic syndromes and aplastic anemia underwent liver and cardiac T2*-weighted unenhanced MRI on a three-tesla MRI scanner, and underwent unenhanced CT scan laterally on a 128-row spectral detector CT. R2* values of the liver, septal muscle, and paraspinal muscle were calculated. Attenuation differences (ΔH) in the liver and myocardium were calculated between the lower (50 keV) and higher (120 keV) energy levels.Results: The liver and cardiac T2* values were 9.54 ± 5.63 ms and 21.41 ± 2.44 ms, respectively. The liver-to-muscle and myocardium-to-muscle T2* value ratios were 0.37 ± 0.23 and 0.79 ± 0.19, respectively. The liver and cardiac ΔH were - 1.13 ± 4.24 HU and 2.22 ± 4.41 HU, respectively. There was a strong linear correlation between the liver R2* and ΔH (r = - 0.832, P < 0.001), but weak correlation existed between the cardiac R2* and ΔH (P = 0.041).Conclusions: Dual-layer detector spectral unenhanced CT seemed to be equally valuable to MRI T2* imaging for evaluating liver iron overload.